Recommendations of the National Advisory Council on Migrant Health, 1993 - National Migrant Resource Program, Inc., Austin, TX.; National Migrant Resource Program, Inc., Austin, TX.; National Advisory Council on Migrant Health, Rockville, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
The 1993 recommendations to the Secretary of Health and Human Services on migrant health emphasize that all available federal and state public service programs be mobilized to also serve farmworkers, and that coordination of efforts among federal agencies and departments take place. The following recommendations offer approaches to secure inclusion of farmworkers in programs designed to assure the safety and health of all Americans: (1) an Interagency Memorandum of Agreement among federal agencies that supports expanded appropriations for construction and subsidy of farmworker housing; (2) an annual appropriation of $100 million for the Migrant Health Program for FY 1994; (3) integration of the mental health needs of farmworkers with the services of all federally funded mental health programs; (4) inclusion of specific farmworker components in special projects designed to strengthen the family; (5) inclusion of farmworkers in health care reform such as reciprocity of Medicaid, national health insurance, provisions for mental health care, and expansion of primary services; (6) expanding community outreach services to farmworkers, including hiring bilingual staff and providing training on maternal and child health to migrant women; (7) establishment of an interagency group to address the enforcement of regulations and laws protecting farmworker health and safety; (8) collaboration of migrant education and Department of Labor programs to train migrant youth in allied and clinical health professions; and (9) research on health status indicators of farmworkers by sex and age. (KS)
Availability: Clearinghouse for Primary Care Information, 4350 East-West Highway, 7th Floor, Rockville, MD 20857 (free).
Sponsoring Agency: Health Resources and Services Administration (DHHS/PHS), Rockville, MD. Bureau of Primary Health Care.
ERIC Note: Photographs will not reproduce well. For a related document, see RC 019 379.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Health Care; Agency Cooperation; Agricultural Laborers; Family Programs; Farm Labor; Federal Programs; Health Care Costs; Health Conditions; Mental Health; Migrant Education; Migrant Health Services; Migrant Housing; Migrant Workers; Occupational Safety and Health; Outreach Programs; Parent Education; Work Environment; National Advisory Council on Migrant Health; Reports, Evaluative; Opinion Papers